Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

Online load balancing on uniform machines with limited migration - Maack, Marten (Operations Research Letters)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; Management Science and Operations Research; Software

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study - Hoffmann, Christina; Schneider, Tamara; Wannous, Chadia; Nyberger, Karolina; Haavardsson, Ingeborg; Gilmore, Brynne; Quigley, Paula; Winkler, Andrea S.; Ludwig, Sabine (Frontiers in Global Women's Health)
Background The COVID-19 pandemic has led to a deepening of existing inequalities and a rollback of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increase female leadership in global health. Here, the aim was to understand how the pandemic affects the private and professional lives of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspectives should be integrated into pandemic preparedness and how a women's network such as WGH helped them to overcome the impact of the pandemic were explored. Methods Qualitative semi-structured interviews were conducted in September 2020 with a sample size of nine highly educated women with a mean age of 42.1 years from the different WGH European chapters. The participants were informed of the study and were formally asked for their consent. The interviews were held in English via an online videoconference platform and lasted 20–25 min each. The interviews were audio recorded and transcribed verbatim. Thematic analysis was conducted according to Mayring Qualitative Content Analysis using MAXQDA. Results The pandemic has both positive and negative effects on the professional and private lives of women. It led to an increased workload and stress as well as pressure to publish on COVID-19-related themes. Increased childcare and household responsibilities represented a double burden. The available space was limited if other family members were also working from home. Positive aspects included more time for family or partners and reduced travel. The participants report on perceived gender differences in the experience of the pandemic. International cooperation is considered to be a key factor for future pandemic preparedness. Being part of a women's network such as WGH was perceived as being very supportive in difficult situations during the pandemic. Conclusion This study provides unique insights into the experiences of women working in global health in different European countries. The COVID-19 pandemic influences their professional and private lives. Perceived gender differences are reported and suggest the need for integrating gender perspectives in pandemic preparedness. Networks for women, such as WGH, can facilitate the exchange of information in crises and provide women with professional and personal support.
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Experimental and finite element method investigation on the compression behaviour of FCCZ and BCC lattice structures of additively manufactured Fe-3Si samples - Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The purpose of this study is to investigate the manufacturability of Fe-3Si lattice structures and the resulting mechanical properties. This study could lead to the successful processing of squirrel cage conductors (a lattice structure by design) of an induction motor by additive manufacturing in the future. Design/methodology/approach The compression behaviour of two lattice structures where struts are arranged in a face-centred cubic position and vertical edges (FCCZ), and struts are placed at body-centred cubic (BCC) positions, prepared by laser powder bed fusion (LPBF), is explored. The experimental investigations are supported by finite element method (FEM) simulations. Findings The FCCZ lattice structure presents a peak in the stress-strain curve, whereas the BCC lattice structure manifests a plateau. The vertical struts aligned along the compression direction lead to a significant increase in the load-carrying ability of FCCZ lattice structures compared to BCC lattice structures. This results in a peak in the stress-strain curve. However, the BCC lattice structure presents the bending of struts with diagonal struts carrying the major loads with struts near the faceplate receiving the least load. A high concentration of geometrically necessary dislocations (GNDs) near the grain boundaries along cell formation is observed in the microstructure. Originality/value To the best of the authors’ knowledge, this is the first study on additive manufacturing of Fe-3Si lattice structures. Currently, there are no investigations in the literature on the manufacturability and mechanical properties of Fe-3Si lattice structures.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (Procedia CIRP ICME)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Investigations on the Influences of the Thermomechanical Manufacturing of Aluminium Auxiliary Joining Elements - Borgert, Thomas; Henke, Maximilian; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The demands on joining technology are constantly increasing due to the consistent lightweight construction and the associated increasing material mix. To meet these requirements, the adaptability of the joining processes must be improved to be able to process different material combinations and to react to challenges caused by deviations in the process chain. One example of a highly adaptable process due to the two-step process sequence is thermomechanical joining with Friction Spun Joint Connectors (FSJCs) that can be individually adapted to the joint. In this paper, the potentials of the adaption in the two-stage joining process with aluminium auxiliary joining elements are investigated. To this end, it is first investigated whether a thermomechanical forming process can be used to achieve a uniform and controlled manufacturing regarding the process variable of the temperature as well as the geometry of the FSJC. Based on the successful proof of the high and good repeatability in the FSJC manufacturing, possibilities, and potentials for the targeted influencing of the process and FSJC geometry are shown, based on an extensive variation of the process input variables (delivery condition and thus mechanical properties of the raw parts as well as the process parameters of rotational speed and feed rate). Here it can be shown that above all, the feed rate of the final forming process has the strongest influence on the process and thus also offers the strongest possibilities for influencing it.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of the filler–matrix adhesion and the effects of conditioning on tensile properties of laser-sintered parts built with polyamide–glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim (Progress in Additive Manufacturing)
In this work, the influence of the filler–matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396 laser sintering system. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, finite element method (FEM) simulations were performed to model the extreme cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler–matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler–matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection-molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.
Keywords: Industrial and Manufacturing Engineering

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depiction is editable and extendable.
Keywords: additive manufacturing; support structures

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Editorial: Remote @ Distance - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Frontmatter - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Estimation of Clinch Joint Characteristics Based on Limited Input Data Using Pre-Trained Metamodels - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (AI)
Given strict emission targets and legal requirements, especially in the automotive industry, environmentally friendly and simultaneously versatile applicable production technologies are gaining importance. In this regard, the use of mechanical joining processes, such as clinching, enable assembly sheet metals to achieve strength properties similar to those of established thermal joining technologies. However, to guarantee a high reliability of the generated joint connection, the selection of a best-fitting joining technology as well as the meaningful description of individual joint properties is essential. In the context of clinching, few contributions have to date investigated the metamodel-based estimation and optimization of joint characteristics, such as neck or interlock thickness, by applying machine learning and genetic algorithms. Therefore, several regression models have been trained on varying databases and amounts of input parameters. However, if product engineers can only provide limited data for a new joining task, such as incomplete information on applied joining tool dimensions, previously trained metamodels often reach their limits. This often results in a significant loss of prediction quality and leads to increasing uncertainties and inaccuracies within the metamodel-based design of a clinch joint connection. Motivated by this, the presented contribution investigates different machine learning algorithms regarding their ability to achieve a satisfying estimation accuracy on limited input data applying a statistically based feature selection method. Through this, it is possible to identify which regression models are suitable to predict clinch joint characteristics considering only a minimum set of required input features. Thus, in addition to the opportunity to decrease the training effort as well as the model complexity, the subsequent formulation of design equations can pave the way to a more versatile application and reuse of pretrained metamodels on varying tool configurations for a given clinch joining task.
Keywords: Industrial and Manufacturing Engineering

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during their utilization. Analyzing these data could enable their manufacturers to generate and exploit insights concerning product performance and user behavior, revealing problems and potentials for improvement. However, research on analyzing use phase data in product planning of manufacturing companies is scarce. Therefore, we conducted an exploratory interview study with decision-makers of eight manufacturing companies. The result of this paper is a detailed description of the potentials and challenges that the interviewees associated with analyzing use phase data in product planning. The potentials explain the intended purpose and generic application examples. The challenges concern the products, the data, the customers, the implementation, and the employees. By gathering the potentials and challenges through expert interviews, our study structures the topic from the perspective of the potential users and shows the needs for future research.
Keywords: Artificial Intelligence; Industrial and Manufacturing Engineering

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuation.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Materials Science (miscellaneous)

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

Mechanical joining in versatile process chains - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Bobbert, Mathias (Production Engineering)
The use of mechanical joining technologies offers the possibility of joining mixed material structures, which are used in particular in lightweight construction. An integrated securing of the joinability in versatile process chains is currently hardly possible as the number of combinable tool variants as well as variable force- and path-based process parameters is infinite. A versatile process chain, i.e. a sequence of all the processes and process steps required for product manufacturing, enables targeted changes to the semi-finished product, the joint, the component or the joining process that exceed the originally planned extend while still ensuring joinability. In detail, it leads to a unique joint with its own mechanical property profile, which, against the background of the resulting infinite number of combinations, makes it impossible to secure the joinability on the conventional experimentally based approach without extensive safety factors. The Transregional Colaborative Research Center 285 (TCRC285), which also initiated this special issue, is intended to enable mechanical joining technology to be versatile in the sense of high application flexibility. This is to be achieved with a numerical representation of the complete process chain from the incoming semi finished product via the joining part production and the joining process to the property profile of the joint in the operating phase. Thus a predictability of the joinability can be achieved and improvements in the individual life cycles of a joint can be realized by grasping the cause-and-effect relationships. On the basis of this knowledge, new possibilities for intervention in the joining process are to be created for the adaptation of the joining processes. With the aid of the methods developed for this purpose, tools will later be available to the end user to substitute the large number of mechanical joining processes or joining task-specific configurations with a smaller number of adaptable processes. This expands the flexibility in material choices, enabling challenges in environmental issues and sustainability to be overcome.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Impact of aging on the energy efficiency of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Becker, Wolfgang; Vrabec, Jadran (Applied Thermal Engineering)
The parameters required to calculate the energy efficiency of household refrigerating appliances (i.e. refrigerators, freezers and their combinations) are determined by standard measurements. According to regulations, these measurements are carried out when the appliances are new. It is known from previous studies that various technical aging mechanisms can increase electrical energy consumption by up to 36 % over a product lifespan of 18 years. In order to determine the time dependence of the energy consumption of household refrigerating appliances, repeated measurements are carried out in this work. Eleven new appliances are examined under standard measurement conditions. After just two years of operation, an additional energy consumption of up to 11 % is determined. Furthermore, 21 older appliances that had previously been measured in new condition are tested again after up to 21 years of operation. For these older appliances, an average increase of energy consumption of 28 % is found. For individual appliances, the maximum increase is 36 %. An aging model is developed on the basis of these measurement results, which may help to predict the aging-related increase of energy consumption of household refrigerating appliances. This model shows an average increase in energy consumption of 27 % for an appliance age of 16 years. Supplemental performance tests of eight compressors do not show any significant aging effects related to these devices after two years of operation. Furthermore, measurements of the thermal conductivity of aged polyurethane foam test samples are carried out and an increase of its thermal conductivity of 26 % over a period of about three years is determined.
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Experimentelle Untersuchung der Tropfenkondensation am chemisch modifizierten Edelstahl‐Drallrohr - Dai, Daokun; Kenig, Eugeny Y.; Numrich, Reiner (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, Lars; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, Martina (Production Engineering)
Abstract In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, René; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, Sören Antonius; Kenig, Eugeny (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, R.; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, S.; Kenig, E.Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Operating window and flexibility of a lab-scale methanation plant - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Feierabend, Lukas; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimental Characterization of 3D Printed Structured Metal Packing with an Enclosed Column Wall - Riese, Julia; Reitze, Arnulf; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Additive manufacturing is a promising tool for tailored solutions in chemical engineering. This applies in particular to the design of lab‐scale packed bed columns. We present experimental results to characterize a lab‐scale 3D printed structured metal packing and compare it to a conventional counterpart. The results indicate that necessary adjustments for the manufacturing process of the metal material have an influence on important operating parameters, resulting in higher specific pressure drop, slightly higher liquid holdup and lower mass transfer efficiency.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Performance of a Laboratory-Scale Methanation Plant with Catalyst Dilution under Dynamic Operating Conditions - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Numerical analysis of conjugate heat transfer within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.; Inguva, Venkatesh (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

A comprehensive framework for sustainable closed-loop supply chain network design - Tavana, Madjid; Kian, Hadi; Nasr, Arash Khalili; Govindan, Kannan; Mina, Hassan (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A multi-distance interval-valued neutrosophic approach for social failure detection in sustainable municipal waste management - Ebadi Torkayesh, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Design and Experimental Investigation of an Additively Manufactured PMSM Rotor - Urbanek, Stefan; Pauline, Frey; Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Ponick, Bernd
Keywords: Elektromotor; Elektromaschine; Additive Fertigung; AF; AM; Additive Manufacturing; DMRC; KAt

Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

The influence of manufacturing processes and optical measurement methods on the damage behavior of HX340LAD micro-alloyed steels - Otroshi, Mortaza; Meschut, Gerson; Nesakumar, Aathavan (Journal of Manufacturing Engineering)
This study deals with the damage behavior of metallic materials by the application of different manufacturing processes and using different optical measurement methods to identify the crack initiation in the damage specimen. The study is intended to highlight the importance of considering manufacturing processes and optical measurement methods in a numerical simulation when analyzing the damage behavior of metallic materials. To describe the damage behavior of the material in the process chain simulations, it is important to calibrate the parameters of damage model more accurately. These parameters are determined using experimental investigation of desired damage specimens. In this regard, a selected damage specimen manufactured by different cutting processes is first experimentally and then numerically investigated. It is shown that the manufacturing process and the optical measurement methods influence the stress state analyzed in the numerical simulation.
Keywords: Damage behaviour; Stress triaxiality; Manufacturing process and Optical measurement

Holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Production Engineering)
Abstract In addition to the classical strength calculation, it is important to design components with regard to fracture mechanics because defects and cracks in a component can drastically influence its strength or fatigue behavior. Cracks can propagate due to operational loads and consequently lead to component failure. The fracture mechanical analysis provides information on stable or unstable crack growth as well as about the direction and the growth rate of a crack. For this purpose, sufficient information has to be available about the crack location, the crack length, the component geometry, the component loading and the fracture mechanical material parameters. The fracture mechanical properties are determined experimentally with standardized specimens as defined by the guidelines of the American Society for Testing and Materials. In practice, however, especially in the context with damage cases or formed material fracture mechanical parameters directly for a component are of interest. However, standard specimens often cannot be extracted at all due to the complexity of the component geometry. Therefore, the development of special specimens is required whereby certain arrangements have to be made in advance. These arrangements are presented in the present paper in order to contribute to a holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Correlation between pre- and post-treatments of additively manufactured 316L parts and the resulting low cycle fatigue behavior - Garthe, Kai-Uwe; Hoyer, Kay-Peter; Hagen, Leif; Tillmann, Wolfgang; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The currently existing restrictions regarding the deployment of additively manufactured components because of poor surface roughness, porosity and residual stresses as well as their influence on the low-cycle fatigue (LCF) strength are addressed in this paper. Design/methodology/approach This study aims to evaluating the effect of different pre- and post-treatments on the LCF strength of additively manufactured 316L parts. Therefore, 316L specimens manufactured by laser powder bed fusion were examined in their as-built state as well as after grinding, or coating with regard to the surface roughness, residual stresses and LCF strength. To differentiate between topographical effects and residual stress-related phenomena, stress-relieved 316L specimens served as a reference throughout the investigations. To enable an alumina coating of the 316L components, atmospheric plasma spraying was used, and the near-surface residual stresses and the surface roughness are measured and investigated. Findings The results have shown that the applied pre- and post-treatments such as stress-relief heat treatment, grinding and alumina coating have each led to an increase in LCF strength of the 316L specimens. In contrast, the non-heat-treated specimens predominantly exhibited coating delamination. Originality/value To the best of the authors’ knowledge, this is the first study of the correlation between the LCF behavior of additively manufactured uncoated 316L specimens in comparison with additively manufactured 316L specimens with an alumina coating.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Concept of a Flexible Wetted‐Wall Column for the Distillation of Specialty Chemicals - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemical Engineering & Technology)
Abstract The trend of increasing product diversity and decreasing production amounts led to the requirement of higher flexibility of production processes of specialty chemicals. Conventional distillation columns, mostly equipped with structured packings, lack the flexibility to handle product changeovers and throughput. Thus, a newly designed distillation column for specialty chemicals is presented. A numerical model was implemented to analyze the potential of the wetted‐wall column. The simulation of the distillation of a binary methanol/water mixture demonstrated that the wetted‐wall column can generate the desired concentration and temperature profiles. Furthermore, analyses of the pressure drop and separation efficiency with the test system chlorobenzene/ethylbenzene were conducted.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Characterization of Liquid-Phase Distribution in 3D Printed Structured Packings with an Enclosed Column Wall - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility analysis for demand-side management in large-scale chemical processes: An ethylene oxide production case study - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Indirect Demand Response Potential of Large-Scale Chemical Processes - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Dynamic Design Optimization for Flexible Process Equipment - Bruns, Bastian; Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Efficient Production of Specialized Polymers with Highly Flexible Small‐Scale Plants - Bruns, Bastian; Becker, Tristan; Riese, Julia; Lier, Stefan; Werners, Brigitte (Chemical Engineering & Technology)
Abstract Shortened product life cycles and increased demand for specialized products lead to more challenges in efficiently satisfying customer needs. Customer demands are increasingly uncertain in terms of type, location, and volume. As a result, more flexible chemical production plants are required. Modular small‐scale plants can be installed in transportation containers and, therefore, offer the flexibility of easy relocation, enabling production close to the customer or supplier. In a mathematical optimization model, the economic benefit of small‐scale plants in the specialty chemicals market of polymer production is analyzed. Different scenarios created from the real data of a chemical company show that the use of small‐scale plants may lead to a significant reduction in total costs that is mainly due to the transportation costs of raw materials and products.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimentelle Untersuchungen zum Tropfenmitriss im Feedeinleitbereich von Destillationskolonnen - Fasel, Henrik; Darvishsefat, Novin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Im Rahmen dieses Beitrags werden experimentelle Untersuchungen zur Tropfenabscheidung im Einleitbereich eines Stoffaustauschapparates für zweiphasige Strömungen vorgestellt. Dafür wurde in einem Versuchsstand im Pilotmaßstab der qualitative Tropfenmitriss für unterschiedliche Tropfenabscheider eines Stoffaustauschapparates vermessen. Die daraus resultierenden Ergebnisse werden in diesem Beitrag hinsichtlich ihrer Aussagekraft zur Vermeidung von Tropfenmitriss diskutiert und bewertet. Darüber hinaus wird ein kurzer Ausblick über simulative Arbeiten zur Bestimmung des Tropfenmitriss gegeben.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

Parameter- und Prozessoptimierung für den additiven Fertigungsprozess im Pulverbett am Beispiel der Legierung Ti6Al4V - Ahlers, Dominik
Die additive Fertigung mittels Laser Powderbed Fusion Verfahren (L-PBF) von Metallen wird zunehmend genutzt, um Funktionsbauteile endkonturnah zu fertigen. Die in der vor-liegenden Arbeit untersuchte Parameter- und Prozessoptimierung liefert einen Beitrag zur wirtschaftlichen Nutzung des L-PBF und zeigt, dass höhere Aufbauraten bei der ganzheit-lichen Betrachtung des Prozesses realisierbar sind. Die Parameter- und Prozessoptimierung erfordert eine Untersuchung des Einflusses der Fertigungs- und Nachbearbeitungsparameter auf das erzeugte Volumen sowie auf die Mikrostruktur und die resultierenden Materialeigenschaften. Das Ziel der vorliegenden Arbeit ist die Entwicklung einer optimierten Prozessführung mit abschließender Bewer-tung der Wirtschaftlichkeit. Mit dem entwickelten Gesamtprozess wird eine um den Faktor 1,6 höhere Aufbaurate erzielt. Des Weiteren wird die Methodik zur Erarbeitung des opti-mierten Prozessfensters beschrieben, sodass die Herangehensweise auf weitere Werk-stoffe angewendet werden kann. Die mechanischen Eigenschaften werden für den stati-schen und dynamischen Lastfall untersucht und mit der Mikrostruktur korreliert. Abschlie-ßend wird die Prozessoptimierung zur Fertigung eines Demonstrators eingesetzt und wirtschaftlich validiert. Die Ergebnisse zeigen, dass durch das hier angewendete Vorge-hen eine Prozesszeitreduktion von 22,5% und eine Kostenreduktion von 11% realisiert werden kann.
Keywords: Additive Manufacturing; SLM

Introduction to the Special Issue “Bargaining” - Haake, Claus-Jochen; Trockel, Walter (Homo Oeconomicus)
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Encrypted polynomial control based on tailored two‐party computation - Schulze Darup, Moritz (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Optimal event‐triggered transmission scheduling for privacy‐preserving wireless state estimation - Lu, Jingyi; Leong, Alex S.; Quevedo, Daniel E. (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Decomposition Reactions of Fe(CO)5, Fe(C5H5)2, and TTIP as Precursors for the Spray-Flame Synthesis of Nanoparticles in Partial Spray Evaporation at Low Temperatures - Gonchikzhapov, Munko; Kasper, Tina (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Separation Units 4.0 – Trennapparate heute und morgen - Riese, Julia; Hoff, Andreas; Stock, Jürgen; Górak, Andrzej; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Die chemische Industrie sieht sich mit gravierenden Herausforderungen konfrontiert: Die Einhaltung der Klimaschutzziele, die Auswirkungen der Energiewende und die zunehmende Bedeutung der Kreislaufwirtschaft treffen die gesamte Wertschöpfungskette. Lösungsansätze von der Prozess‐ über die Apparateebene bis hin zum Einzelphänomen sind notwendig, um die Wettbewerbsfähigkeit dieses zentralen Industriezweigs zu erhalten. In diesem Beitrag werden aktuelle Entwicklungen und zukünftige Handlungsfelder in der Trenntechnik, die für diese Herausforderungen wertvolle Beiträge leisten können, dargestellt.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Transformable Decentral Production for Local Economies with Minimized Carbon Footprint - Pannok, Maik; Finkbeiner, Marco; Fasel, Henrik; Riese, Julia; Lier, Stefan (ChemBioEng Reviews)
Abstract Due to high energy‐intensive processes and a dependence on carbon‐based materials, the process industry plays a major role in climate change. Therefore, the substitution of fossil resources by bio‐based resources is indispensable. This leads to challenges arising from accompanying changes of the type, amount and location of resources. At the same time, transformable production systems are currently in the focus of research addressing the required flexibility. These systems which consist of modular production and logistics units offer the possibility to adapt flexibly in volatile conditions within dynamic supply chains. Hence, this work compiles elements for environmental sustainability, which minimize the carbon footprint in the process industry: transformable production systems, the utilization of bio‐based resources, carbon dioxide and renewable energy as well as the application of these elements in decentral production networks. Finally, possible use cases are determined based on the combination of these elements through a multi‐criteria analysis.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Modular Production with Bio‐Based Resources in a Decentral Production Network - Finkbeiner, Marco; Pannok, Maik; Fasel, Henrik; Riese, Julia; Lier, Stefan (Chemie Ingenieur Technik)
Abstract The change in process industry from fossil resources to alternative feedstock is indispensable due to the scarcity of resources and global warming. This leads to new challenges for the production systems. On the market side, rapid innovation is accompanied by shorter product life cycles leading to an increasing uncertainty of demand in terms of product type, volume and location. Therefore, the following five elements are combined into a concept to address these challenges: transformable production systems, local bio‐based resources, CO 2 as feedstock, renewable energy and decentral production network with local economies.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Comparison of the Operating Range of a Wetted‐Wall Column with a Packed Column for Distillation - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract In this paper, a newly designed distillation column consisting of a wetted wall with a rectangular cross section is analyzed and compared with a conventional packed column with regard to the operating range of both apparatuses. As expected, the pressure drop is considerably lower in the wetted‐wall column and, therefore, it offers a higher range of operation. However, in the wetted‐wall column, the separation efficiency decreases rapidly with increasing F factors. This effect can be overcome by the serial connection of two wetted‐wall columns.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

New Column Design to Enhance Flexibility: Concept for Hydrodynamic Characterization - Fasel, Henrik; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract This study presents a new and innovative sieve tray design for a more flexible operation of separation columns in terms of possible throughput. The advantage of this new tray design is to ensure an optimal operation for varying feed flow rates and constant separation efficiencies for different load ranges. The aim of this work is to give a short introduction and an outlook to the investigation of the functionality of the designed trays. Moreover, the general design of the new trays, first results for CFD simulations of the dry pressure drop and the experimental setup are presented.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility of Power‐to‐Gas Plants: A Case Study - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract Due to the increasing share of renewable energies in the power sector, the need for energy storage and flexible performance is rising. This study provides an in‐depth investigation of the flexibility of a Power‐to‐Gas plant for the production of synthetic natural gas. Model‐based analysis is conducted for the individual technologies PEM electrolysis, MEA absorption and fixed‐bed methanation as well as for the continuously operated process. This study reveals that the Power‐to‐Gas plant offers a capacity flexibility of 87–125 %, corresponding to 4.79–6.88 MW electrical input power.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Challenges and Opportunities to Enhance Flexibility in Design and Operation of Chemical Processes - Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Flexibility receives increased interest in chemical engineering and is discussed as one measure to deal with upcoming challenges for the chemical industry. In this paper, different types of flexibility are presented, and flexibility needs are illustrated. The focus is on the evaluation and classification of available solutions to enhance flexibility. Solutions and future challenges across all length scales of chemical engineering are discussed: from tailored catalyst properties to decoupling of processes by means of storage.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Analysis of Capacity Potentials in Continuously Operated Chemical Processes - Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract A method is proposed to evaluate capacity potentials in continuously operated chemical processes. In the main part of the analysis, the operating windows of the equipment are examined based on detailed steady‐state simulations. The method is applied to a case study of the production process of ethylene oxide as a large‐scale commodity chemical. Results show the limitations continuously operated processes are confronted with. However, opportunities to enlarge or shift the operating window of apparatuses applied are determined.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

On the Influence of Thermal Histories within Part Cakes on the Polymer Laser Sintering Process - Josupeit, Stefan
Polymer Laser Sintering (LS) is one of the most used Additive Manufacturing (AM) technologies for the tool-less production of polymer parts. The raw material is a polymer powder which is melted layerwise by the use of laser energy. Especially for the production of single parts, small series, individualized and complex structures, the technology is yet established in few branches. However, inhomogeneous and hardly controllable thermal effects during manufacturing limit the build reproducibility. The present work focuses on temperatures within so-called part cakes, their time dependency and their influence on process quality. Therefore, a temperature measurement system is implemented into a commercial laser sintering machine. Based on the experimental data a model to simulate heat transfer within part cakes is set up. Individual thermal histories during processing are successfully correlated with position dependent powder ageing effects. Another focus is on the analysis of a recycling optimized material. First results of correlations between thermal histories and part properties are shown in order to provide an outlook to further research. The data and knowledge gained through this work can be used to understand thermal effects in greater depth and to increase the process quality via optimizations.
Keywords: Additive Manufacturing; Polymer Laser Sintering; Polymer Science

Putting 5G into Production: Realizing a Smart Manufacturing Vertical Scenario - Schneider, Stefan Balthasar; Peuster, Manuel; Behnke, Daniel; Marcel, Müller; Bök, Patrick-Benjamin; Karl, Holger (European Conference on Networks and Communications (EuCNC))
As 5G and network function virtualization (NFV) are maturing, it becomes crucial to demonstrate their feasibility and benefits by means of vertical scenarios. While 5GPPP has identified smart manufacturing as one of the most important vertical industries, there is still a lack of specific, practical use cases. Using the experience from a large-scale manufacturing company, Weidmüller Group, we present a detailed use case that reflects the needs of real-world manufacturers. We also propose an architecture with specific network services and virtual network functions (VNFs) that realize the use case in practice. As a proof of concept, we implement the required services and deploy them on an emulation-based prototyping platform. Our experimental results indicate that a fully virtualized smart manufacturing use case is not only feasible but also reduces machine interconnection and configuration time and thus improves productivity by orders of magnitude.
Keywords: 5g; vertical; smart manufacturing; nfv

"Producing Cloud-Native": Smart Manufacturing Use Cases on Kubernetes - Schneider, Stefan Balthasar; Peuster, Manuel; Hannemann, Kai; Behnke, Daniel; Müller, Marcel; Bök, Patrick-Benjamin; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN) Demo Track)
Building on 5G and network function virtualization (NFV), smart manufacturing has the potential to drastically increase productivity, reduce cost, and introduce novel, flexible manufacturing services. Current work mostly focuses on high-level scenarios or emulation-based prototype deployments. Extending our previous work, we showcase one of the first cloud-native 5G verticals focusing on the deployment of smart manufacturing use cases on production infrastructure. In particular, we use the 5GTANGO service platform to deploy our developed network services on Kubernetes. For this demo, we implemented a series of cloud-native virtualized network functions (VNFs) and created suitable service descriptors. Their light-weight, stateless deployment on Kubernetes enables quick instantiation, scalability, and robustness.
Keywords: 5G; NFV; Smart Manufacturing; Cloud-Native; Kubernetes

The value of signals: Do self-declaration and certification generate price premiums for organic and biodynamic wines? - Fanasch, Patrizia; Frick, Bernd (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Modeling and Validating Fixed‐Bed Reactors: A State‐of‐the‐Art Review - Stegehake, Carolin; Riese, Julia; Grünewald, Marcus (ChemBioEng Reviews)
Abstract Modeling of heat and mass transfer in fixed‐bed reactors for heterogeneously catalyzed gas phase reactions is possible using different methods. Homogeneous and heterogeneous continuum models as well as particle resolved modeling of fixed‐bed reactors show high potential for application. Considering those approaches, advantages and disadvantages as well as underlying assumptions and boundary conditions are discussed. Additionally, methods for experimental validation are presented and discussed focusing on the two‐dimensional homogeneous models.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering

Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance? - Wang, Zhi; Reimsbach, Daniel; Braam, Geert (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Optimization of the energy supply in the plastics industry to reduce the primary energy demand - Dunkelberg, Heiko; Wagner, Johannes; Hannen, Conrad; Schlüter, Alexander; Phan, Long; Hesselbach, Jens; Lin, Cheng-Xian (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Modeling and Validating Fixed‐Bed Reactors: A State‐of‐the‐Art Review - Stegehake, Carolin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Es stehen vielfältige Methoden zur Beschreibung der Wärme‐ und Stofftransportvorgänge in Festbettreaktoren für die Durchführung von heterogen katalysierten Gasphasenreaktionen zur Verfügung. Neben den homogenen und heterogenen Kontinuumsmodellen kann auch der partikelaufgelösten Modellierung ein hohes Anwendungspotenzial zugewiesen werden. Für die Methoden werden die Vor‐ und Nachteile sowie Annahmen und Randbedingungen dargestellt und diskutiert. Zusätzlich werden die Möglichkeiten zur experimentellen Validierung diskutiert, wobei der Fokus dabei auf den besonders verbreiteten zweidimensionalen, homogenen Kontinuumsmodellen liegt.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Investigation of the structure and spread rate of flames over PMMA slabs - Rakesh Ranga, H.R.; Korobeinichev, O.P.; Harish, A.; Raghavan, Vasudevan; Kumar, A.; Gerasimov, I.E.; Gonchikzhapov, M.B.; Tereshchenko, A.G.; Trubachev, S.A.; Shmakov, A.G. (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Investigation of the structure and spread rate of flames over PMMA slabs - Rakesh Ranga, H.R.; Korobeinichev, O.P.; Harish, A.; Raghavan, Vasudevan; Kumar, A.; Gerasimov, I.E.; Gonchikzhapov, M.B.; Tereshchenko, A.G.; Trubachev, S.A.; Shmakov, A.G. (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Experimental setup of a cascaded two-stage organic Rankine cycle - Dubberke, Frithjof H.; Linnemann, Matthias; Abbas, Wameedh Khider; Baumhögger, Elmar; Priebe, Klaus-Peter; Roedder, Maximilian; Neef, Matthias; Vrabec, Jadran (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Innovative scaling strategies for a fast development of apparatuses by modular process engineering - Lier, Stefan; Riese, Julia; Cvetanoska, Gordana; Lesniak, Anna Katharina; Müller, Stephan; Paul, Sarah; Sengen, Laura; Grünewald, Marcus (Chemical Engineering and Processing - Process Intensification)
Keywords: Industrial and Manufacturing Engineering; Process Chemistry and Technology; Energy Engineering and Power Technology; General Chemical Engineering; General Chemistry